Certain Subclasses of Multivalent Analytic Functions. (21st July 2013) - Cang, Yi-Ling; Liu, Jin-Lin
Abstract : Two new subclasses H p, k ( λ, A, B ) and Q p, k ( λ, A, B ) of multivalent analytic functions are introduced. Distortion inequalities and inclusion relation for H p, k ( λ, A, B ) and Q p, k ( λ, A, B ) are obtained. Some results of the partial sums of functions in these classes are also given.